Impact of protein kinase CK2 inhibitors on proliferation and differentiation of neural stem cells - Bender, Melanie; Schäfer, Karl Herbert (Heliyon, 2017)
Abstract Background Protein kinases play central roles in cell and tissue development. Protein kinase CK2, an ubiquitously expressed serine/threonine kinase has severe impacts on embryo- and spermatogenesis. Since its role in neurogenesis has so far only been investigated in very few studies, we analysed the role of CK2 in neural stem cells by using two specific inhibitors. Methods Neural stem cells were isolated from the subventricular zone of neonatal mice, using a neurosphere approach. Proliferation of the neurospheres, as well as their differentiation was investigated with and without inhibition of CK2. Changes in proliferation were assessed by counting the number and measuring the diameter of the neurospheres. Furthermore, the absolute cell numbers within the neurospheres were estimated. Differentiation was induced by retinoic acid in single cells after dissociation of the neurospheres. CK2 was inhibited at consecutive time points after induction of the differentiation process. Results CK2 inhibition reduced the amount and size of proliferating neurospheres dose dependently. Adding the CK2 inhibitor CX-4945 at the start of differentiation we observed a dose-dependent effect of CX-4945 on cell viability and glia cell differentiation. Adding quinalizarin, a second CK2 inhibitor, at the start of differentiation led to an elevated level of apoptosis, which was accompanied by a reduced neural differentiation. Adding the CK2 inhibitors at 72 h after the start of differentiation had no effect on stem cell differentiation. Conclusion: Inhibition of CK2 influences early gliogenesis in a time point and concentration dependent manner. General significance The use of a CK2 inhibitor significantly affects the neural stem cell niche.